2014
DOI: 10.1016/j.virol.2014.07.036
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of nonstructural protein 9 with retinoblastoma protein benefits the replication of genotype 2 porcine reproductive and respiratory syndrome virus in vitro

Abstract: The nonstructural protein 9 (Nsp9) of porcine reproductive and respiratory syndrome virus (PRRSV) is a RNA-dependent RNA polymerase (RdRp) that plays a vital role in viral replication. This study first demonstrated that the Nsp9 of genotype 2 PRRSV interacted with cellular retinoblastoma protein (pRb), and Nsp9 co-localized with pRb in the cytoplasm of PRRSV-infected MARC-145 cells and pulmonary alveolar macrophages (PAMs). Next, the overexpression of truncated pRb was shown to inhibit the PRRSV replication an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…Many host cellular factors have been proved to interact with nsp9 and regulate the replication or RNA synthesis of PRRSV (Dong et al, 2014;Liu et al, 2016;Zhao et al, 2015). In another aspect, our results also suggested that the virulence of mutant viruses could be more remarkable decreased by the nsp10 of HB-1/3.9, although the replication efficiency changes were not observed.…”
Section: Discussionmentioning
confidence: 48%
“…Many host cellular factors have been proved to interact with nsp9 and regulate the replication or RNA synthesis of PRRSV (Dong et al, 2014;Liu et al, 2016;Zhao et al, 2015). In another aspect, our results also suggested that the virulence of mutant viruses could be more remarkable decreased by the nsp10 of HB-1/3.9, although the replication efficiency changes were not observed.…”
Section: Discussionmentioning
confidence: 48%
“…Recent studies have indicated the role of Nsp9 in the replication of PRRSV by interacting with host cellular proteins (J. Dong et al, 2014). However, more studies are required to uncover a possible network of host cellular proteins interacting with this nonstructural protein in the PRRSV replication.…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature indicated that the interaction of Nsp9 with endogenous cellular annexin A2 is beneficial for PRRSV replication in MARC-145 cells (J. . Our latest work showed that the interaction of Nsp9 with cellular retinoblastoma protein (pRb) contributes the replication of genotype 2 PRRSV in vitro (Dong et al, 2014). Therefore, further exploring the interaction of Nsp9 with host cellular proteins is necessary for fully understanding the mechanisms associated with the replication regulation and pathogenesis of PRRSV.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, several host proteins have been reported to interact with PRRSV Nsp9. On the one hand, interaction between Nsp9 and cellular annexin A2, retinoblastoma protein (pRb), DDX5 positively regulates the replication of PRRSV in vitro, demonstrating that PRRSV heavily relies on host cellular proteins to complete life cycle (Dong et al, 2014;Li et al, 2014a;Zhao et al, 2015). On the other hand, recent literature indicated that the interaction of Nsp9 with SUMO E2 conjugating enzyme Ubc9 and cellular protein interleukin-2 enhancer binding factor 2 (ILF2) through its RdRp domain resulted in a significantly decrease of virus titers, indicating that cells utilize host antiviral factors as defense mechanisms to limit PRRSV infection Wen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%